2019
DOI: 10.1103/physrevx.9.021047
|View full text |Cite
|
Sign up to set email alerts
|

Pair-Density-Wave Order and Paired Fractional Quantum Hall Fluids

Abstract: The properties of the isotropic incompressible ν = 5/2 fractional quantum Hall (FQH) state are described by a paired state of composite fermions in zero (effective) magnetic field, with a uniform px +ipy pairing order parameter, which is a non-Abelian topological phase with chiral Majorana and charge modes at the boundary. Recent experiments suggest the existence of a proximate nematic phase at ν = 5/2. This finding motivates us to consider an inhomogeneous paired state -a px + ipy pair-density-wave (PDW) -who… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 98 publications
0
10
0
Order By: Relevance
“…Note added in proof: Recently, there appeared an interesting study that considers a different generalization of the LOFF state for systems to the p x +ip y case [28]. In contrast to our work, there the system has nonalternating chirality but forms inhomogeneous states of stripes of the alternating overall sign of the order parameter with a given chirality.…”
mentioning
confidence: 67%
“…Note added in proof: Recently, there appeared an interesting study that considers a different generalization of the LOFF state for systems to the p x +ip y case [28]. In contrast to our work, there the system has nonalternating chirality but forms inhomogeneous states of stripes of the alternating overall sign of the order parameter with a given chirality.…”
mentioning
confidence: 67%
“…The distinguishing feature between the physics we present and that of, for instance, Ref. [56] is that we present FCIs as a platform in which to study intertwining of TO and BSO, in that they do not compete with nor are even independent of one another, but rather arise from a common microscopic origin, namely the interplay between the pairing of composite fermions and the commensurability of the lattice and magnetic length scales.…”
Section: Introductionmentioning
confidence: 86%
“…Related phenomena have been exhibited in recent experiments [53][54][55], which revealed a competition between pairing and nematicity in continuum Landau levels. A subsequent theoretical study [56] proposed a p x + ip y PDW state of composite fermions as a possible explanation for this observation. The distinguishing feature between the physics we present and that of, for instance, Ref.…”
Section: Introductionmentioning
confidence: 94%
“…However, phase transitions between the two distinct classes of phases, such as the transition from a fractional quantum Hall state to the nematic, remain rare and present an opportunity for further theoretical development. [216][217][218][219][220][221] One may gain further insight into the transition by investigating it in the upper spin branch of the second Landau level. Such studies confirmed a qualitatively similar phase transition at filling factor ν = 7/2.…”
Section: High Pressure Studies Of the Second Landau Levelmentioning
confidence: 99%